2002
DOI: 10.1021/cm0107272
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Albumin and Fibrinogen on Calcium Phosphate Formation on Sol−Gel-Derived Titania Coatings in Vitro

Abstract: The sol-gel technique provides a method to produce porous titania (TiO 2 ) coatings, which are known to induce bone-like hydroxyapatite formation on their surface in vitro. In this study, the calcium phosphate formation (in vitro bioactivity) on a sol-gel-derived titania coating was investigated in vitro in a simulated body fluid in the presence and absence of albumin (BSA) and fibrinogen (Fib) in solution as well as the effect of surface immobilized proteins on the biomineralization process. The effect of pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 44 publications
2
58
1
Order By: Relevance
“…Thus, the introduction of proteins into the inorganic media used to study CaP formation gives indirect information on the transformation mechanism of the initially formed CaP phase(s) to the resulting CaP phase(s). In a recent article, 20 it was suggested that the formation of bonelike apatite on sol-gel-derived titania coatings also occurs via the dissolution/reprecipitation mechanism. It was suggested that the presence of proteins (BSA and Fib) does not inhibit the CaP nucleation but rather inhibits the growth stage of the initially formed CaP to bonelike apatite.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the introduction of proteins into the inorganic media used to study CaP formation gives indirect information on the transformation mechanism of the initially formed CaP phase(s) to the resulting CaP phase(s). In a recent article, 20 it was suggested that the formation of bonelike apatite on sol-gel-derived titania coatings also occurs via the dissolution/reprecipitation mechanism. It was suggested that the presence of proteins (BSA and Fib) does not inhibit the CaP nucleation but rather inhibits the growth stage of the initially formed CaP to bonelike apatite.…”
Section: Discussionmentioning
confidence: 99%
“…The Ca/P ratio of the uncharged CaP was lower (Ͻ1) than that of the charged CaP (near 1.3), corresponding to amorphous and poorly crystalline CaP phases, respectively. 20 In SBF solutions (SBF ϩ BSA, SBF ϩ Fib, SBF ϩ Plasma, and BSA added after 2 days), in which calcium and phosphate concentrations did not decrease during the observation time of 2 weeks, the calculated Ca/P ratio was closer to 1, and no charging effect was observed, suggesting that amorphous CaP has formed.…”
Section: Chemical Surface Analysis (In Vitro)mentioning
confidence: 94%
“…The sol-gel technique is a wet chemical process used to produce metallic oxide glass, bioceramic and bioactive titania-like surfaces [28][29][30]. Sol-gel coatings have demonstrated good bioactivity due to abundant hydroxyl (OH) groups on the surface that promote nucleation of calcium apatite or formation of mineralized matrix by osteoblasts [31][32][33][34]. Thin film oxide coatings can also be prepared by a stepwise surface sol-gel process (SSP) [35].…”
Section: Introductionmentioning
confidence: 99%
“…[1,29] Although the formation and deposition of amyloid-like protein nanofibrils in the human body are generally not desired, protein nanofibrils can play a very important role in the field of tissue engineering, [30] and biomedicine. [31,32] The intrinsic characteristics of the fg such as self assembly, [33] promotion of cell adhesion and the dual role in calcium phosphate formation [34] give fg an important role in the field of biomaterials science, [35] as fg is a potential building block for preparation of advanced biomaterials. [1] Furthermore, some properties of the protein nanofibrils are useful for nanotechnology.…”
mentioning
confidence: 99%